Enhancing Instruction Through Cross-disciplinary Instruction - McKenzie, Tammy; Burrack, Frederick W. (My University, 2010)
When we select literature to study and perform in band, there are often opportunities neglected that can enhance our students’ understanding of the music. One of these opportunities involves collaboration with other disciplines. As we design teaching plans, consideration should be given to relationships that can enhance our students’ understanding of a musical piece. A cross-disciplinary approach focuses on concepts common between disciplines within the study of each discipline to increase student understanding and relevance.2 This instructional approach can bridge understandings based around the musical works selected for your band.
Keywords: Music education; High school; Curriculum; Visual arts